Integrated multi-omics analysis unravels the floral scent characteristics and regulation in “Hutou” multi-petal jasmine - Jingping Fang; Linwei Zhou; Qinchang Chen; Jinbin Wang; Ying Zhuang; Shaoqing Lin; Hansong Yan; Kai Zhao; Jisen Zhang; Robert J. Henry (Communications Biology)
Abstract The multi-petal “Hutou” jasmine (Jasminum sambac var. Trifoliatum) is highly valued for bonsai cultivation and landscape design, however, the aroma profile and mechanisms underlying floral scent formation remain elusive. In this study, we generate a nearly complete telomere-to-telomere (T2T) genome assembly of “Hutou” jasmine (487.45 Mb with contig N50 of 38.93 Mb). Metabolomic profiling unveils that 16 significantly differential volatiles (SDVs) may play a crucial role in the formation of flower aroma. Among them, five scented SDVs, particularly α-farnesene and pentanoic acid 1-ethenyl-1,5-dimethyl-4-hexenyl ester, contribute to the characteristic aroma profile of “Hutou” jasmine flowers. Weighted gene co-expression network analysis (WGCNA) identifies HTWRKY41, HTWRKY53, and HTHSP90 as the hub genes potentially regulating the production of these 16 metabolites. The expression of selected genes and duplication events drive the increased relative content of major sesquiterpenoids in terpenoid biosynthetic pathway. Four structural genes (BEAT3, BSMT1, BPBT2, and BPBT3) are potentially implicated in the emission of downstream key volatile esters (benzyl acetate, methyl benzoate, and benzyl benzoate) in the phenylpropanoids synthesis. Our integrated dataset of genomics, transcriptomics, and metabolomics present here provides a theoretical basis for the practical utilization of fragrance and genetic improvement in horticultural applications of “Hutou” jasmine.